The Rise in Demand for Special Education in Ontario, Canada: A Focus on French-Language Schools - Guenot, Brittany; Jaber, Lindsey S. (Journal of Teaching and Learning, 2022)
Over the past several decades, teachers have been increasingly challenged with a greater diversity of learning profiles within their classrooms. Historically, within Ontario, Canada, students who did not learn effectively through traditional methods were labelled and separated into alternate learning environments. Legislation and policy transformation have resulted in greater inclusion and stigma reduction. Changes to formal and informal identification processes have also increased the number of students accessing special education services. This conceptual paper examines the challenges arising from students’ changing learning needs, with a specific focus on the French classroom. Issues related to the Individual Education Plan, the formal identification processes, and the inconsistency inherent to special education terminology and teachers’ preparation concerning differentiated learning and resources in special education are explored. Further, employing Katz and colleagues’ (Hymel & Katz, 2019; Katz, 2013; Katz & Sokal, 2016) three-block model of universal design for an inclusive classroom as a framework, a case study from a French-language secondary school in Ontario, Canada, is examined to determine systemic gaps that need to be addressed to achieve the goal of fully inclusive classrooms that promote successful learning experiences for all students.